Porous Ionic Polymers as a Robust and Efficient Platform for Capture and Chemical Fixation of Atmospheric CO2 - Sun, Qi; Jin, Yingyin; Aguila, Briana; Meng, Xiangju; Ma, Shengqian; Xiao, Feng‐Shou (ChemSusChem, 2017)
Direct use of atmospheric CO2 as a C1 source to synthesize high‐value chemicals through environmentally benign processes is of great interest, yet challenging. Porous heterogeneous catalysts that are capable of simultaneously capturing and converting CO2 are promising candidates for such applications. Herein, a family of organic ionic polymers with nanoporous structure, large surface area, strong affinity for CO2, and very high density of catalytic active sites (halide ions) was synthesized through the free‐radical polymerization of vinylfunctionalized quaternary phosphonium salts. The resultant porous ionic polymers (PIPs) exhibit excellent activities in the cycloaddition of epoxides with atmospheric CO2, outperforming the corresponding soluble phosphonium salt analogues and ranking among the highest of known metal‐free catalytic systems. The high CO2 uptake capacity of the PIPs facilitates the enrichment of CO2 molecules around the catalytic centers, thereby benefiting its conversion. We have demonstrated for the first time that atmospheric CO2 can be directly converted to cyclic carbonates at room temperature using a heterogeneous catalytic system under metal‐solvent free conditions. Moreover, the catalysts proved to be robust and fully recyclable, demonstrating promising potential for practical utilization for the chemical fixation of CO2. Our work thereby paves a way to the advance of PIPs as a new type of platform for capture and conversion of CO2. CO2‐trapping PIPs: A family of phosphonium based porous ionic polymers (PIPs) that are capable of simultaneously capturing and converting CO2, exhibits extraordinary performance in CO2 fixation under mild conditions. These PIPs feature a nanoporous structure, large surface area, a strong affinity for CO2, and high density of active sites.